APLIKASI METODE OPTIMASI STRUKTUR UNTUK MENAIKKAN KEKAKUAN PINTU AIR G2517 - I Wayan Suweca; Satryo Soemantri; Suhariyono Suhariyono (Mesin, 1999)
During its operation, Slide-Water-Gate structure, receive an excessive vibration due to resonance effect caused by water current. To avoid this undesirable effect, in this paper we propose the application of structural optimization method to modify the initial structure. The goal of this optimization is to maximize the ï¬rst natural frequencies so that the resonance effect can be minimized and the weight of structure is remained constant. The optimization is conducted by using the ANSYS 5.4 ï¬nite element program package.